2010
DOI: 10.1111/j.1365-2966.2009.15675.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the red giant and dusty environment of the recurrent nova RS Ophiuchi following the 2006 eruption

Abstract: We present near-infrared spectroscopy of the recurrent nova RS Ophiuchi (RS Oph) obtained on several occasions after its latest outburst in 2006 February. The 1-5 μm spectra are dominated by the red giant, but the H I, He I and coronal lines present during the eruption are present in all our observations. From the fits of the computed infrared spectral energy distributions to the observed fluxes, we find T eff = 4200 ± 200 K for the red giant. The first overtone CO bands at 2.3 μm, formed in the atmosphere of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
(42 reference statements)
0
15
1
Order By: Relevance
“…Besides the X-ray observations, data on RS Oph were also collected in the radio (O'Brien et al 2006;Kantharia et al 2007;Eyres et al 2009), IR (Monnier et al 2006;Das et al 2006;Evans et al 2007aEvans et al , 2007bChesneau et al 2007;Lane et al 2007;Banerjee et al 2009;Rushton et al 2010;Brandi et al 2009), and optical bands (Hachisu et al 2006;Worters et al 2007;Bode et al 2007;Munari et al 2007;Brandi et al 2009). Hachisu et al (2007) discussed the temporal evolution of the RS Oph SSS X-ray light curve, but did not include any detailed consideration of the spectral characteristics or their evolution; nor did they include the effects of interstellar and (changing) circumstellar absorption on their conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the X-ray observations, data on RS Oph were also collected in the radio (O'Brien et al 2006;Kantharia et al 2007;Eyres et al 2009), IR (Monnier et al 2006;Das et al 2006;Evans et al 2007aEvans et al , 2007bChesneau et al 2007;Lane et al 2007;Banerjee et al 2009;Rushton et al 2010;Brandi et al 2009), and optical bands (Hachisu et al 2006;Worters et al 2007;Bode et al 2007;Munari et al 2007;Brandi et al 2009). Hachisu et al (2007) discussed the temporal evolution of the RS Oph SSS X-ray light curve, but did not include any detailed consideration of the spectral characteristics or their evolution; nor did they include the effects of interstellar and (changing) circumstellar absorption on their conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with that expected after the first dredge-up (Charbonnel 1994) and suggests that the RG in RS Oph has undergone the first dredge-up and has evolved beyond this evolutionary stage. In spectra shown by Rushton et al (2010), numerous emission lines are visible in the spectral regions around 1.0-1.8 μm. These form in material ejected in the 2006 eruption or in the shocked or ionized RG wind, in each case well away from the photosphere of the secondary.…”
Section: Discussionmentioning
confidence: 97%
“…The properties of the dust shell around RS Oph have been discussed by Evans et al (2007), van Loon (2008) and Woodward et al (2008). and Rushton et al (2010) have shown that the 2 μm spectral region of RS Oph is not affected by emission from the hot (∼500-600 K) dust known to currently envelop RS Oph, which is likely a permanent feature of the system. As this dust emission becomes prominent longwards of 3 μm, we are justified in carrying out our analysis for the dust-free case.…”
Section: The Effect Of Circumstellar Dustmentioning
confidence: 98%
See 2 more Smart Citations